2016
DOI: 10.9790/5933-704033136
|View full text |Cite
|
Sign up to set email alerts
|

Determining The Centers of Economic Growth And Regional Development Using Scalogram Analysis (An Empirical Study In West Halmahera Regency, Indonesia)

Abstract: Each region has potentials and economic advantages that can be used as the source of its regional growth. The capability of each region to promote its own growth depends on its economic competitive advantages. This study is aimed to determine the centers of economic growth and regional development in West Halmahera Regency in the North Moluccas Province. The data used for analysis is secondary data which were collected using documentation method and internet browsing. The method of analysis used is scalogram a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Tebing Tinggi District and Merlung District are identified as secondary growth centers, corresponding to the third hierarchy. This aligns with research conducted by Jacob and Hasan (2016), which found that almost all of the nine sub-districts studied were in the third hierarchy. The third hierarchy describes an area with a low level of development and a relative scarcity of service facilities, situated far from the sub-districts activity center (Anwar et al, 2022).…”
Section: The Center Of Growth For Tanjung Jabung Barat Regencysupporting
confidence: 89%
“…Tebing Tinggi District and Merlung District are identified as secondary growth centers, corresponding to the third hierarchy. This aligns with research conducted by Jacob and Hasan (2016), which found that almost all of the nine sub-districts studied were in the third hierarchy. The third hierarchy describes an area with a low level of development and a relative scarcity of service facilities, situated far from the sub-districts activity center (Anwar et al, 2022).…”
Section: The Center Of Growth For Tanjung Jabung Barat Regencysupporting
confidence: 89%
“…Determining the growth poles is a serious concern and is needed to encourage the sustainability of economic growth between regions [42]. For this reason, there is a logical demonstration, and rationality of the analysis used (Klassen's Typology and Gravity Index) is needed to answer the study problem.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies use scalogram analysis to determine service centers in an urban area [22]. In the cited authors' research, a linear programming method is used to design the optimal location selection model for the construction of charging stations.…”
Section: Literature Reviewmentioning
confidence: 99%